(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
This aim of this study is to determine the effect of using propolis extract as edible coating for beef on chemical characteristics consisting of moisture content, malondialdehyde value and antioxidant activity at room temperature storage. This research used randomized design with 4 treatments and 3 replications. The treatment applied in this study was immersing the meat in propolis extract with different concentrations, that are 0.5%, 1.0%, and 1.5% propolis coating. Coating meat with the addition of propolis extract was able to have a significant effect at a concentration of 0.5% on water content and the antioxidant activity of coating meat (P <0.05). The addition of propolis extract at various concentrations can maintain the quality of beef by reducing rancidity during storage. The increasing concentration of propolis extract caused the decreasing of MDA value.